2017
DOI: 10.1089/sur.2016.090
|View full text |Cite
|
Sign up to set email alerts
|

Local Probiotic Therapy with Lactobacillus plantarum Mitigates Scar Formation in Rabbits after Burn Injury and Infection

Abstract: Background: Infection is the most common complication in burn-injured patients and is believed to contribute to the hypertrophic scarring frequently observed in such injury. Pseudomonas aeruginosa is a common pathogen in burn wound infection. We examined the effect of local probiotic therapy with Lactobacillus plantarum on the severity of the scarring following burn wounding and infection with P. aeruginosa in a rabbit model. Methods: Full-thickness burn wounds were inoculated with control vehicle or L. planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 36 publications
4
45
0
2
Order By: Relevance
“…This regenerative process is potentially hampered by infection, which can be of fungal or bacterial origin, with the most prevalent microorganisms being Staphylococcus aureus (gram-positive bacteria), Pseudomonas aeruginosa [36,37] (gram-negative bacteria) and Candida spp. (fungi) [3].…”
Section: Pathophysiology Of Burn Wound Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This regenerative process is potentially hampered by infection, which can be of fungal or bacterial origin, with the most prevalent microorganisms being Staphylococcus aureus (gram-positive bacteria), Pseudomonas aeruginosa [36,37] (gram-negative bacteria) and Candida spp. (fungi) [3].…”
Section: Pathophysiology Of Burn Wound Infectionsmentioning
confidence: 99%
“…(fungi) [3]. Infection constitutes a major concern, as the production of a biofilm in the extracellular matrix protects the microorganisms against conventional antibiotics and is highly associated with hypertrophic scar [37]. After a burn injury, with the thermal destruction of the skin and the haemostasis phase, the burn wound surface takes the form of an avascular necrotic tissue with high protein content, which results in impaired immune cells migration and provides a favourable environment to microbial invasion and colonization.…”
Section: Pathophysiology Of Burn Wound Infectionsmentioning
confidence: 99%
“…in vitro, but also demonstrated inhibition of Pseudomonas colonization and improved tissue repair in a burn mouse model [ 101 ]. In the presence of infection, L. plantarum containing probiotics reduced collagen accumulation in Pseudomonas infected burn wounds, ultimately decreasing the extent of scarring [ 102 ]. In chronic wounds, a randomized clinical trial revealed the potential advantageous healing properties of probiotics in DFUs with significant reductions in ulcer length and depth, in addition to improved glycemic control [ 103 ].…”
Section: Modulating the Microbiome: Clinical Implications For Wounmentioning
confidence: 99%
“…e studies investigated burn wounds, ischemic wounds, and skin lesions. ree studies each used mouse [61,68,78] and rat models [76,80,81] and two studies used rabbit models [77,79]. Local application of probiotics was used for six studies and only two studies included local injections [61,78] of probiotics.…”
Section: Animal Studies On Use Of Probiotics For Wound Infectionsmentioning
confidence: 99%